2013
DOI: 10.1021/je400110c
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria of the Systems CO2 + Styrene, CO2 + Safrole, and CO2 + Styrene + Safrole

Abstract: This work reports phase equilibrium experimental data of binary and ternary systems involving carbon dioxide (CO2), 5-(2-propenyl)-1,3-benzodioxole (safrole), and ethenylbenzene (styrene). The experimental phase equilibrium data were measured using a high-pressure variable-volume view cell based on the static synthetic method in the temperature range of (303 to 343) K, at several CO2-overall compositions and pressures up to 16 MPa. For ternary system measurements, solutions of safrole and styrene with styrene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Windmann et al improved the Peng–Robison equation of state (PR EoS) with the quadratic mixing rule or the Huron–Vidal mixing rule to correlate the experimental data for the solubility of nitrogen in acetone and oxygen in acetone and noted that the results of the quadratic mixing rule were very similar to those from the Huron–Vidal mixing rule. Tenório Neto et al found that the experimental data were satisfactorily represented by the PR EoS with the quadratic mixing rule. The results confirmed that PR EoS with the quadratic mixing rule or the Huron–Vidal mixing rule can be used for good prediction of the oxygen (nitrogen)–organic solvent equilibrium.…”
Section: Introductionmentioning
confidence: 97%
“…Windmann et al improved the Peng–Robison equation of state (PR EoS) with the quadratic mixing rule or the Huron–Vidal mixing rule to correlate the experimental data for the solubility of nitrogen in acetone and oxygen in acetone and noted that the results of the quadratic mixing rule were very similar to those from the Huron–Vidal mixing rule. Tenório Neto et al found that the experimental data were satisfactorily represented by the PR EoS with the quadratic mixing rule. The results confirmed that PR EoS with the quadratic mixing rule or the Huron–Vidal mixing rule can be used for good prediction of the oxygen (nitrogen)–organic solvent equilibrium.…”
Section: Introductionmentioning
confidence: 97%
“…The experimental apparatus and procedure were based on the static synthetic method, whose use is widely documented in the literature. A diagram of the experimental apparatus used in this work for phase equilibrium measurements is shown in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…All experimental data of the measured phase equilibria were recorded in a variable volume view cell based on the static synthetic methodology. An apparatus description can be found in the literature. …”
Section: Methodsmentioning
confidence: 99%